A Potential Diagnostic and Prognostic Biomarker TMEM176B and Its Relationship With Immune Infiltration in Skin Cutaneous Melanoma - Jiang, Linlan; Yang, Yanyin; Liu, Fangming; Ma, Mingyue; Gao, Jie; Sun, Lu; Chen, Yuwen; Shen, Zan; Wu, Duojiao (Frontiers in Cell and Developmental Biology, 2022)
Abstract Background: Melanoma is one of the most aggressive malignancies. The search for new and effective biomarkers facilitates early diagnosis and treatment, ultimately improving the prognosis of melanoma patients. Although the transmembrane protein TMEM176B has been linked to a number of cancers, its role in cancer immunity remains unknown. Methods: The expression levels of TMEM176B in normal tissues and several cancers, including Skin Cutaneous Melanoma (SKCM), were collected from TCGA. We used Receiver operating characteristic and Kaplan–Meier survival curves and performed regression analysis to elucidate the link between TMEM176B and clinicopathological features of SKCM in order to determine the prognostic significance of TMEM176B in SKCM. We then used the GEPIA and STRING websites to search for proteins and associated top genes that may interact with TMEM176B and enriched them for analysis. The link between TMEM176B and immune cells infiltration was then investigated using TIMER, CIBERSORT algorithm and GSVA package of R (v3.6.3). Finally, animal tests were conducted to confirm the expression of TMEM176B and its influence on T-cell immune infiltration. Results: TMEM176B expression was considerably elevated in SKCM compared to normal tissues. Particularly, TMEM176B expression was also linked to pathological stage, tumor ulceration and radiation therapy sensitivity. Patients with elevated TMEM176B expression had a better prognosis, according to the survival analysis. The majority of tumor infiltrating lymphocytes (TILs) especially T cells in SKCM was positively linked with TMEM176B expression. Our animal experiments also verified that the T-cell infiltration was significantly inhibited in local melanoma tissue of TMEM176B knockdown mice. At the same time deleting TMEM176B accelerated tumor progress and impaired T cells effector function. Conclusions: Upregulated expression of TMEM176B in SKCM is linked to a better prognosis and it could be employed as a diagnostic and prognostic marker for the disease. It may serve as a target for SKCM immunotherapy by regulating CD8+T cells although it requires more evidence.